2012
DOI: 10.3892/mmr.2012.1037
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of von Willebrand factor gene polymorphism and coronary heart disease

Abstract: To characterize von Willebrand factor (vWF) gene polymorphisms at site A1381T and the correlation of plasma vWF levels with coronary heart disease, the vWF genotypes at site A1381T were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in patients diagnosed with coronary heart disease and normal controls (n=110 per group), and plasma vWF levels were measured by enzyme‑linked immunosorbent assay. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…In the presence of 1mM egtazic acid (to inhibit Ca 2+ -ATPase), 0.5mM ouabain (to inhibit the Na + /K + -ATPase), and 10mM azide (to inhibit mitochondrial ATPase), the ATPase activity measured for the P-glycoprotein containing membranes can be attributed to P-glycoprotein which represents 20% of the total membrane protein, the basal ATPase activity determined in the absence of any added agent was about 84.7 ± 5.13 μmol• min -1 •g -1 protein. The dose-response curve of guggulsterone showed a stimulatory characteristic, which was similar to previous results (Nabekura et al, 2008;Xu et al, 2012.). However, verapamil revealed a biphasic characteristic.…”
Section: Effect Of Guggulsterone On the Basal P-glycoprotein Atpase Asupporting
confidence: 86%
See 2 more Smart Citations
“…In the presence of 1mM egtazic acid (to inhibit Ca 2+ -ATPase), 0.5mM ouabain (to inhibit the Na + /K + -ATPase), and 10mM azide (to inhibit mitochondrial ATPase), the ATPase activity measured for the P-glycoprotein containing membranes can be attributed to P-glycoprotein which represents 20% of the total membrane protein, the basal ATPase activity determined in the absence of any added agent was about 84.7 ± 5.13 μmol• min -1 •g -1 protein. The dose-response curve of guggulsterone showed a stimulatory characteristic, which was similar to previous results (Nabekura et al, 2008;Xu et al, 2012.). However, verapamil revealed a biphasic characteristic.…”
Section: Effect Of Guggulsterone On the Basal P-glycoprotein Atpase Asupporting
confidence: 86%
“…The ATPase activity of P-glycoprotein was stimulated by guggulsterone, as well as verapamil, known substrate of P-glycoprotein. Our previous study also showed that guggulsterone could stimulate P-glycoprotein ATPase activity in a dose-dependent manner using purified reconstituted P-glycoprotein membrane (Xu et al, 2012). Although plasma membranes isolated from multidrug-resistant cell lines contains lower percent of P-glycoprotein as fraction of total membrane protein than that of purified reconstituted P-glycoprotein, there is no significant difference of the effect of guggulsterone on P-glycoprotein ATPase activity between them.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We considered all case-control studies that examined the association of the adiponectin polymorphisms with CHD in Chinese Han populations. [8][9][10][11][12][13][14][15][16][17][18] Sources included MEDLINE, Chinese National Knowledge Infrastructure (CNKI) and Chinese WanFang database (up to January 2011). The search strategy was based on the combination of 'adiponectin gene', 'apM1', 'polymorphism', 'coronary heart disease' and 'China/Chinese'.…”
Section: Identification and Eligibility Of Relevant Studiesmentioning
confidence: 99%
“…Eleven studies [8][9][10][11][12][13][14][15][16][17][18] probing the association between adiponectin gene polymorphism and CHD were identified. They all met the eligible criteria.…”
Section: Study Characteristicsmentioning
confidence: 99%